-37-7r=-3(5r-9)

Simple and best practice solution for -37-7r=-3(5r-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -37-7r=-3(5r-9) equation:


Simplifying
-37 + -7r = -3(5r + -9)

Reorder the terms:
-37 + -7r = -3(-9 + 5r)
-37 + -7r = (-9 * -3 + 5r * -3)
-37 + -7r = (27 + -15r)

Solving
-37 + -7r = 27 + -15r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '15r' to each side of the equation.
-37 + -7r + 15r = 27 + -15r + 15r

Combine like terms: -7r + 15r = 8r
-37 + 8r = 27 + -15r + 15r

Combine like terms: -15r + 15r = 0
-37 + 8r = 27 + 0
-37 + 8r = 27

Add '37' to each side of the equation.
-37 + 37 + 8r = 27 + 37

Combine like terms: -37 + 37 = 0
0 + 8r = 27 + 37
8r = 27 + 37

Combine like terms: 27 + 37 = 64
8r = 64

Divide each side by '8'.
r = 8

Simplifying
r = 8

See similar equations:

| 12x/3(x-1) | | 92-y=214 | | 56=4(3n-1) | | -11*-11*-11= | | 3c^2+12c=-15c | | -2(2x+7)-7(-8x-6)=-76 | | -4(3t-4)+6t=2t-3 | | 12=23-n | | (w+4)(2w+4)=2w^2+12 | | 2x+50+2x+30=180 | | -36=-9(x+8) | | 2(x-3)=3y-1 | | 2p-14+3(p+5)=81 | | 2(4x)+2(36-5x)=p | | 2(x-4)=-4x+4 | | 729-16-2= | | 2m^2=14m | | 2x+9*2x=6 | | 4.5x+5.2= | | an=17+(n-1)(-3) | | 2y+22=28 | | 19+3x-1=15x-10-5x | | (3x-2)=8 | | 3(-4+r)=-21 | | 7x+17=80 | | an=17+(n-1)-3 | | 4(x)-17=31 | | 1/8=1/1/8 | | 1/3×5/8 | | 3(2+m)=12 | | F(x)=-5+1 | | 1/8=11/8/n |

Equations solver categories